Social and obstetric factors associated with the way of delivery: reality of a maternity school in the interior of the northeast (Research, Society and Development, 2021)
The study aims to identify the social and obstetric factors associated with the mode of delivery of postpartum women attending a public maternity hospital located in the interior of the state of Sergipe, in the northeast region. This is a cross-sectional study that included 1,149 postpartum women in the immediate period, carried out between November 2016 and December 2019, who underwent functional kinesiological assessment for physical therapy care. Descriptive analysis and binary logistic regression were performed using the mode of delivery as the dependent variable. The results showed that the prevalence of cesarean deliveries was of 49.24% (n=565). Most puerperal women were young, married, primiparous and with elementary education. Vaginal delivery was associated with postpartum women with married marital status (OR, 10.463; 95%CI, 2.367-46.254), multipregnancy (OR, 9.54; 95% CI, 7.19-12.65), multiparous (OR, 8.79; 95%CI, 6.66-11.62), with no pain (OR, 2.08; 95%CI, 1.63-2.65), no comorbidities (OR,1.69, 95%CI, 1.23-2.28), number of prenatal consultations from one to seven (OR, 1.534; 95%CI, 1.18-1.98), and without difficulty to breastfeed (OR, 1.373, 95%CI, 1.04-1.80). The cesarean delivery route was associated with abortion in primiparae (OR, 1.69; 95%CI, 1.192-2.415) and education at the elementary level. (OR, 2.99; 95%CI, 1.403-6.411). It is concluded that social factors (education level and marital status), obstetric factors (parity, number of pregnancies, comorbidities, obstetric care) and immediate puerperal complaints (pain and difficulty in breastfeeding) were associated with the modes of delivery.